LEISHMANICIDAL INSIGHTS FROM PINE RESINE DERIVATIVES - Barbosa, Regis Silveira; Oliveira, Ana Cláudia Cerqueira; Naves, Mário Mateus; Julioti, Michelle de Aguiar Pimenta; da Silva, Marília Vitória Franco; Vaz, Carolina Ferreira; Couto, Laércio; Júnior Dias, Herbert; Magalhães, Lizandra Guidi; Heleno, Vladimir Constantino Gomes (Seven Editora, 2025)
Due to the known potential of diterpenes to display biological activities, the aim of this work was to produce amide derivatives from dehydroabietic acid, naturally occurring in pine resins and evaluate them against Leishmania amazonensis. Our venture into the derivatives production led us to eight different amides which were properly identified and characterized by Nuclear Magnetic Resonance spectroscopy. Biological assays were carried out with all derivatives and the natural precursor against promastigote forms of L. amazonensis. Results show that two derivatives can be considered of better activity than the precursor against this parasite. This opens future perspectives to further explore that kind of diterpenes against Leishmania species.DOI: https://doi.org/10.56238/sevened2025.036-144